The differences of parasitemia in Plasmodium berghei infected mice treated with extract of mango parasite leaves with Artemisinin combination - Muhammad Zulkifly Tasman; Heny Arwati; Nurina Hasanatuludhhiyah; Puspa Wardhani (Universitas Muhammadiyah Surabaya, 2023)
Malaria is a disease transmitted through the bite of a female Anopheles mosquito caused by the Plasmodium parasite. Plasmodium has been reported to become resistant to artemisinin. Thus, the study on the ethanol extract of mango parasite leaves/Dendrophthoe pentandra (MP) on P. berghei-infected BALB/c mice with and without artemisinin combination (MP+A) was conducted. This study is experimental laboratory research with a post-test only design. The percent parasitemia in mice treated with ethanol extract of MP and MP+A leaves decreased. There was no difference in the spleen index in mice given ethanol extract of MP, and MP+A leaves with p = 0.203 and the spleen weight of mice with p = 0.134 (significance: p <0.005). Pearson Correlation test showed a correlation between spleen index with parasitemia and spleen weight with parasitemia; however, there was no correlation between body weight and parasitemia. The ethanol extracts of MP and MP+A leaves had significant antimalarial activity, and the difference in the percent parasitemia between groups was significant but not so far. The spleen index value was not affected by the ethanol extract of MP and MP+A leaves, but the percent parasitemia was affected.